A conservation and taxonomic assessment of the least shrew (Cryptotis parvus) complex through rangewide phylogeographic analyses and population genomics - Galfano, Thomas (Kansas State University, 2021)
Cryptotis is a speciose genus of shrews with a broad New World distribution from southern Canada to Northern South America. Cryptotis consists of 49 currently recognized species and is traditionally split into six distinct species groups. North American Least shrews (Cryptotis parvus) belong to the parvus group of shrews which includes six recognized species. Cryptotis parvus (sensu stricto) is broadly distributed across central and eastern North America from southern Ontario, Canada, and the Great Lakes, south to Florida and west through tall and short grass prairies to their western extent just east of the Rocky Mountains in the United States. Within C. parvus there are two recognized subspecies: Cryptotis p. floridanus found throughout the coastal Carolinas south through Florida, and Cryptotis p. parvus, found throughout the rest of the range. However, these shrews are locally rare, and little is yet known about their evolutionary history. New populations occurring peripheral to the recorded distribution of C. parvus have been repeatedly discovered since the 1980s, progressively extending the known range of this species westward. In the west, potentially isolated populations relying on declining mesic grassland habitats have led to the shrew’s listing as threatened within New Mexico, but this listing has elicited additional genetic analyses to qualify existing species, and infraspecific relationships, including rangewide systematics, connectivity/gene flow, and regional genetic diversity and demography. While this taxon is currently recognized as a single species with two subspecies, I hypothesize that cryptic diversity is present that will challenge the existing taxonomy. Preliminary rangewide assessments of C. parvus indicate populations in Florida may be distinct from the rest of the range, but these results were based on early genetic techniques, and the evidence for delimiting distinct taxa was not conclusive. Among western peripheral populations in New Mexico, previous research postulated that multiple distinct lineages may exist, reflecting recent westward range extension in the north but relictual persistence in the south. Given that all peripheral populations are currently considered a single taxon for management, my research aims to inform the most appropriate units of analysis for applied conservation within this species. In this research, I performed a rangewide phylogeographic study, using Cytochrome-B data (n=106) and reduced representation genome sequencing (~10,000 SNP loci; n=64), to 1) assess relationships across the range of C. parvus with the inclusion of additional closely related species, and 2) investigate the genetic legacy of New Mexico populations within the broader context of the species complex. Both mitochondrial and nuclear data indicate populations in Florida are highly divergent and support the hypothesis that C. parvus is made up of multiple cryptic taxa. Phylogenomic analyses of nuclear data support the high divergence seen in Florida populations and also indicate that southern New Mexico populations constitute a distinct and endemic infraspecific taxon of C. parvus reflecting both long-term isolation and adaptive divergence. Although this taxon may warrant recognition as a unique subspecies, it does not align with any currently recognized subspecies of C. parvus, and without the inclusion of diagnostic morphology, genomic data alone are not at this point robust for designating taxonomy below the level of species. Instead, I have assessed the relative contributions of adaptive versus neutral evolution for defining different evolutionary units of analysis that reflect locally adaptive diversity or population divergence as a consequence of independent (allopatric) differentiation, respectively. My results highlight a complex history of diversification of least shrews that lends support for shared faunal (and floral) evolution across the Great Plains, and more broadly through North America.
Keywords: Cryptic species; Phylogenomics; ddRADseq; Conservation genetics; Peripheral populations